Risk Management in New Product Development of Kombucha Cascara: A Coffee Waste-Based Local Product Case Study in Karangpring Village Jember: Manajemen Risiko New Product Development Pada Kombucha Cascara: Studi Kasus Produk Kreatif Lokal Berbasis Limbah Kopi di Desa Karangpring Jember - Riski Kuara; Deltaningtyas Tri Cahyaningrum; Dewi Kurniawati; Wenny Dhamayanthi (Journal of Business Management, 2025)
This research aims to analyze risk management in the new product development (NPD) of cascara kombucha, a fermented drink made from coffee husk waste, in Karangpring Village, Jember.  Kombucha cascara is a local creative product innovation that offers health benefits and a sustainable solution by transforming waste into value-added products.  The research method used is Failure Modes, Effects, and Criticality Analysis (FMECA) to identify risks and the House of Risk (HOR) to analyze and design risk mitigation strategies.  The research results indicate that the main risks in NPD kombucha cascara include supply chain instability, raw material quality, and product distribution.  The recommended mitigation strategies include adding alternative suppliers, utilizing adequate logistics services, and installing temperature and humidity control systems.  This research significantly contributes to supporting the development of innovative products and providing sustainable solutions for the waste-based food and beverage industry.  In addition, this research also provides recommendations for future NPD development, particularly in the context of locally-based creative waste products.